Reliability of a portable fixed frame dynamometry system used to test lower limb strength in elite Australian Football League players - Ransom, M.; Saunders, S.; Gallo, T.; Segal, J.; Jones, D.; Jones, M.; Milanese, S. (Journal of Science and Medicine in Sport, 2020)
Objectives: Deficits in strength of lower limb musculature have been associated with increased injury risk in a variety of athletic populations. As medical and performance staff seek to better understand the association between hip and knee strength measures and injury risk, measurement tools with high reliability and utility are required to profile and manage athletes effectively. The purpose of this study was to investigate the test-retest reliability of a portable fixed frame dynamometry system used to assess hip and knee strength of an elite Australian Football League team. Design: Case series. Methods: Maximum voluntary isometric strength of the hip abductors, hip adductors and knee flexors of 41 elite male Australian Football League footballers (mean age=23.7±4.1 years, height=189.2±7.0cm, weight=88.6±8.4kg) were tested during preseason training. Tests were performed one week apart on the same training day of a standard preseason week. Results: Test-retest reliability was very high for left hip adduction (ICC 0.958), right hip adduction (ICC 0.955), left hip abduction (ICC 0.957), right hip abduction (ICC 0.945), left knee flexion (ICC 0.927) and right knee flexion (ICC 0.923). Furthermore, standard errors of measurement in per cent (SEM%) ranged from 3.21 to 5.03%, and minimal detectable change (MDC) from 3.93 to 6.65kg for the different hip and thigh strength measures, making it possible to determine small changes in strength at the individual level. Conclusions: This study demonstrated very high reliability when testing maximal voluntary isometric hip and knee strength using a portable fixed dynamometry system (KangaTech) in an elite male Australian Football League setting.